Safety and efficacy of esketamine combined with propofol or ciprofol sedation for electroconvulsive therapy in patients with major depressive disorder: protocol for a randomized, double-blind, controlled trial with factorial design - Zhang, Yuan; Su, De-zhen; Chen, Rong; Xia, Zhong-yuan; Peng, Yan-ling; Weng, Shen-hong; Meng, Qing-tao (Frontiers in Pharmacology, 2025)
IntroductionElectroconvulsive therapy (ECT) is one of the main strategies for major depressive disorder (MDD). Recently, the use of esketamine in the treatment of depression due to the rapid antidepressant effects has been highlighted. The present study hypothesizes that 1) adjunctive esketamine during ECT will produce greater improvement in depressive symptoms compared to placebo; 2) the esketamine–ciprofol combination will demonstrate superior antidepressant efficacy and fewer adverse events relative to the esketamine–propofol combination.Methods and analysisThis is a prospective, randomized, double-blind, placebo-controlled, repeated-measures trial with factorial design, planned to be conducted in Renmin Hospital of Wuhan University from 1 May 2024 to 31 May 2025. A total of 168 cases with MDD undergoing scheduled ECT will be randomized in a ratio of 1:1:1:1 to receive propofol or ciprofol sedation with or without esketamine (0.25 mg/kg) treatment. The primary outcome is the changes from baseline to day 28 in HAMD-24. Secondary outcomes include the rates of response (a 50% or greater reduction in HAMD-24 total scores) and remission (a score of 8 or less in the HAMD-24 total scores), along with the rate of reduction in the HAMD-24 total scores from baseline, at the end of the trial. In addition, the incidence of adverse events and the details of ECT will also be recorded. Standard intention-to-treat (ITT) analyses will be performed after handling missing data using multiple imputation methods. The predefined subgroup analysis on primary outcomes will be conducted according to age and sex. The generalized estimating equation (GEE) will be utilized to analyze the outcomes. This study will address two critical questions in ECT practice: whether ECT with adjunctive esketamine achieves clinically superior outcomes to ECT alone, and whether anesthetic choice (ciprofol versus propofol) modulates the antidepressant efficacy of esketamine. The findings from this randomized controlled trial (RCT) will provide novel evidence to optimize sedation regimens during ECT in patients with MDD, specifically addressing the risk–benefit ratio of adjunctive esketamine administration.Ethics and disseminationThis trial was approved by the local Institutional Review Board (No. WDRY2024-K018) and conducted following the guidelines of the Declaration of Helsinki. Results of this trial will be publicly disclosed in a peer-reviewed journal.Clinical Trial Registrationclinicaltrials.gov, identifier ChiCTR2400083664.